The role of design patterns in the development and legal assessment of lawful technologies - Ernestine Dickhaut; Mahei Manhai Li; Andreas Janson; Jan Marco Leimeister (Electronic Markets, 2022)
Novel technologies such as smart personal assistants integrate digital services into everyday life. These services use personal data to offer personalized services. While they are subject to special data protection regulations at the time of development, there are few guidelines describing the transition from legal requirements to implementation. To reduce risks, services depend on external legal assessments. With developers and legal experts often missing either legal or technical knowledge, the challenge lies in bridging this gap. We observe that design patterns support both developers and legal experts, and we present an approach in which design patterns are leveraged to provide twofold value for both developers and legal experts when dealing with novel technologies. We conducted a revelatory case study for smart personal assistants and scaffolded the case interpretation through cognitive fit theory. On the basis of the findings, we develop a theoretical model to explain and predict the twofold value of design patterns to develop and assess lawful technologies.
Keywords: D47; D8; K1; 620; Design pattern; Smart personal assistants; Lawful system development; Digital services; Law simulation study